Observing complexity : systems theory and postmodernity - Rasch, William, 1949-; Wolfe, Cary (University of Minnesota Press, 2000)
Brings the major concepts and foremost thinkers of systems theory into interaction with the major figures of postmodern theory. The format is multiplex and opena rich montage, including interviews, exemplary essays, and staged dialogues.